2011
DOI: 10.1039/c0nr00680g
|View full text |Cite
|
Sign up to set email alerts
|

Graphene based gene transfection

Abstract: Graphene as a star in materials research has been attracting tremendous attentions in the past few years in various fields including biomedicine. In this work, for the first time we successfully use graphene as a non-toxic nano-vehicle for efficient gene transfection. Graphene oxide (GO) is bound with cationic polymers, polyethyleneimine (PEI) with two different molecular weights at 1.2 kDa and 10 kDa, forming GO-PEI-1.2k and GO-PEG-10k complexes, respectively, both of which are stable in physiological solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
401
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(409 citation statements)
references
References 44 publications
6
401
0
2
Order By: Relevance
“…Unbounded PEI was then removed by centrifugation and washing. Constructed GO‐PEI was stale in both saline (0.9% NaCl) cell medium without obvious agglomeration as reported 18. Since naked miRNAs are instable and easy to be catalyzed by enzymes, the best way for miRNA delivery is through a plasmid vector.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Unbounded PEI was then removed by centrifugation and washing. Constructed GO‐PEI was stale in both saline (0.9% NaCl) cell medium without obvious agglomeration as reported 18. Since naked miRNAs are instable and easy to be catalyzed by enzymes, the best way for miRNA delivery is through a plasmid vector.…”
Section: Resultsmentioning
confidence: 58%
“…For GO‐PEI complexes preparation, PEI solution (1 mg mL −1 ) was slowly added into GO solution (0.1 mg mL −1 ) in 10 min. After ultrasonication for about 10 min, the mixture was stirred overnight, washed 3–5 times with deionized (DI) water by centrifugation, and then redispersed in DI water 18. GO‐PEI complexes were then mixed with miR‐7b GV159 plasmid in deionized water at the N/P ratios of 20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified GO is used for gene delivery purposes. Polyethylenimine (PEI) modifies the surface of GO sheets and thus makes it ready for cellular gene delivery through covalent conjugation and electrostatic interaction [58] for plasmid DNA (pDNA) stacking. GO is attached covalently to the linear chain [35] and branched chain [59].…”
Section: Gene Deliverymentioning
confidence: 99%
“…These studies have shown the use of graphene in microbial fuel cells, 249 graphene as a scaffold for bacterial growth, 228 as well as the use of bacteria as a graphene oxide reducing agent. 250,251 Various in vitro toxicity studies have been conducted to determine the toxicity of graphene towards cancer [234][235][236][237][238] and human cell lines. 229,239 The cytotoxicity towards the cancer cell lines A549 was shown to depend largely on the cell culture medium components.…”
Section: Environmental and Biological Toxicity Of Graphenementioning
confidence: 99%